Chemical profiles and biological properties of methanol extracts of Allium pallens L. from different localities in Turkey - Emir, Ahmet; Emir, Ceren (Archives of Biological Sciences, 2020)
Paper description: Due to their wide range of biological effects, phenolic compounds are one of the most significant secondary metabolite groups of plants. The determination of phenolics, total bioactive compounds, and antioxidant and enzyme inhibitory activities of Allium pallens L. was carried out by chromatographic and spectrophotometric methods. Stem parts of A. pallens collected from different locations were rich in phenolics and possessed notable biological activities. A. pallens may be a natural source of bioactive compounds and help to advance in vivo research on diseases related to cholinesterase and tyrosinase inhibition. Abstract: Many species of the Allium genus, principally the cultivated forms, are widely used as vegetables, spices and natural therapeutics due to their beneficial health properties. This study aimed to identify the phenolic composition and biological activities of the bulb, stem and flower parts of Allium pallens L., collected from two different localities. A total of 28 phenolic compounds were investigated by LC-ESI-MS/MS, and gallic acid, 4-hydroxybenzoic acid, and benzoic acid were found to be the major phenolic compounds in the plants from both locations. Total phenolic- and flavonoid-content analyses of samples were carried out using spectrophotometry, and the stem extracts were found to be rich in phenolics. DPPH, ABTS, FRAP and CUPRAC assays were used to determine the antioxidant capacities of the extracts. A linear relation was observed between the phenolic contents of the extracts and their antioxidant activities, and the stem extracts of plants from both locations were found to have potent antioxidant capacity. The inhibitory activities of the extracts against acetylcholinesterase, butyrylcholinesterase and tyrosinase were determined using a 96-well microplate reader. The anti-butyrylcholinesterase activity of the extracts was found to be the highest. The outcomes of these investigations were further explored, and the underlying structure of multivariate data was revealed using principal component analysis. This study presents the distribution of chemical constituents and biological activities of the different parts of A. pallens, and also contributes to further investigations of Allium species. https://doi.org/10.2298/ABS200226013E Received: February 26, 2020; Revised: April 20, 2020; Accepted: April 20, 2020; Published online: April 20, 2020 How to cite this article: Emir A, Emir C. Chemical profiles and biological properties of methanol extracts of Allium pallens L. from different localities in Turkey. Arch Biol Sci. 2020;72(2):193-201.